A quantitative coupling degree model for source-to-sink (S2S) system through entropy weight-coupling theory: a case study of the Chengbei Low Uplift area, offshore Bohai Bay Basin, Eastern China - Ji, Xinyuan; Xu, Chunqiang; Li, Wenrui; Wang, Qiming; Hu, Hewei (Frontiers in Earth Science, 2025)
IntroductionSource-to-sink (S2S) analysis plays a crucial role in sedimentological studies, serving as an effective tool for reconstructing sediment-routing processes and guiding hydrocarbon exploration. Numerous studies on S2S systems have focused on examining the correlations among subsystems by statistically analyzing and characterizing the parameters of the S2S system. However, few studies focus on quantifying the degree of interaction (i.e., the coupling degree) between multiple sub-S2S systems, leading to a biased understanding of coupling mechanisms, S2S processes, and exploration potential.MethodsTo address this issue, we developed a quantitative model for coupling degree based on entropy weight-coupling theory (EW-CT), providing a novel framework for systematically evaluating the interactions within S2S systems. The Paleogene Chengbei Low Uplift (CBLU) in the Bozhong Sag, offshore Bohai Bay Basin (OBBB) in eastern China, serves as a case study to validate the model and examine the multi-hierarchy S2S coupling mechanisms as well as the exploration potential in an ancient uplift system.ResultsThe main findings are: (1) the CBLU is divided into five second-level S2S systems (P/Q/R/S/T), with the study area (S) further subdivided into six third-level sub-S2S systems (S1–S6); (2) there is a positive correlation between EW-CT values and coupling degree in the S2S systems; (3) the coupling degree of the eastern braided-delta S2S systems (S4–S6) exceeds that of the northern fan-delta S2S systems (S1–S3); (4) among the braided-delta S2S systems, the S5 system shows the greatest exploration potential.DiscussionImportantly, this study underscores the broader applicability of the EW-CT model across diverse geological settings, offering a quantitative approach to assess S2S interactions and identify high-potential areas for hydrocarbon exploration. The proposed framework has the potential to enhance sedimentological research and improve exploration strategies in various sedimentary basins worldwide, bridging the gap between theoretical studies and practical applications.